Spies on the Sidelines: The High-Stakes World of NFL Espionage - Bryant, Kevin, (Rowman & Littlefield Publishers, 2022)
The first book to fully explore the extraordinary covert actions NFL teams are willing to take in order to win. Spies disguised as priests. Secret surveillance of targets’ movements. Radio frequency jamming. Tapped telephones. These might sound like acts of espionage right out of the Cold War or a spy movie—but in fact came straight from the National Football League. In Spies on the Sidelines: The High-Stakes World of NFL Espionage, Kevin Bryant provides the first in-depth investigation of spying in professional football, as well as the countermeasures utilized to defend against these threats. Spanning across all teams and eras, Bryant shines a light on the shady world of NFL reconnaissance—from clandestine photography and hidden draft prospects to listening devices and stolen documents—along with the permissible, if sometimes questionable, spy techniques teams utilize day in and day out to gain an advantage over their opponents. Written by a former Special Agent with decades of experience collecting and safeguarding information for the Department of Defense, Spies on the Sidelines reveals that, behind the game-day action, professional football can be as cloak-and-dagger as American intelligence agencies. This fascinating and expansive compilation of NFL spy anecdotes exposes the extraordinary measures teams are willing to take in order to win.